Predicting bending moment in crown of soil-steel structure built as ecological crossing for animals = Prognozowanie momentów zginających w kluczu konstrukcji gruntowo-powłokowych budowanych jako przejścia ekologiczne dla zwierząt - Mumot, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper concerns soil-metal structures made of a thin shell (usually - corrugated steel) and soil backfill. During backfilling significant deformations of the structure can be observed (the upper part of the shell buckles and its width narrows). This phenomenon results in a subsequent prestressing effect during placing the backfill material above the crown of the structure.
Keywords: konstrukcje gruntowo-powłokowe; przejście ekologiczne; stal falista; deformacja konstrukcji; soil-steel structures; ecological crossing; corrugated steel; soil backfill; deformation; bending moment